Development of Quality Measures in Cirrhosis by the Practice Metrics Committee of the American Association for the Study of Liver Diseases. Issue 4 (12th March 2019) - Kanwal, Fasiha; Tapper, Elliot B.; Ho, Chanda; Asrani, Sumeet K.; Ovchinsky, Nadia; Poterucha, John; Flores, Avegail; Ankoma‐Sey, Victor; Luxon, Bruce; Volk, Michael
Abstract : Health care delivery is increasingly evaluated according to quality measures, yet such measures are underdeveloped for cirrhosis. The Practice Metrics Committee of the American Association for the Study of Liver Diseases was charged with developing explicit process‐based and outcome‐based measures for adults with cirrhosis. We identified candidate measures from comprehensive reviews of the literature and input from expert clinicians and patient focus groups. We conducted an 11‐member expert clinician panel and used a modified Delphi method to systematically identify a set of quality measures in cirrhosis. Among 119 candidate measures, 46 were identified as important measures to define the quality of cirrhosis care, including 26 process measures, 7 clinical outcome measures, and 13 patient‐reported outcome measures. The final process measures captured care processes for ascites (n = 5), varices/bleeding (n = 7), hepatic encephalopathy (n = 4), hepatocellular cancer (HCC) screening (n = 1), liver transplantation evaluation (n = 2), and other care (n = 7). Clinical outcome measures included survival, variceal bleeding and rebleeding, early‐stage HCC, liver‐related hospitalization, and rehospitalization within 7 and 30 days. Patient‐reported outcome measures covered physical symptoms, physical function, mental health, general function, cognition, social life, and satisfaction with care. The final list of patient‐reported outcomes was validated in 79 patients with cirrhosis from nine institutions in the United States. Conclusion: We developed an explicit set of evidence‐based quality measures for adult patients with cirrhosis. These measures are a tool for providers and institutions to evaluate their care quality, drive quality improvement, and deliver high‐value cirrhosis care. The quality measures are intended to be applicable in any clinical care setting in which care for patients with cirrhosis is provided.